The state of the ‘People’ pillar by 2022 A partial ordering-based analysis of the sustainable development goals 1–5 - Lars Carlsen (World Development Sustainability, 2023)
Based on the data provided in the 2022 Sustainable Development Report the so-called People pillar, i.e., the Sustainable Development Goals (SDGs) 1–5 are studied to elucidate the state of compliance as well as the trends in development for the 193 countries included in the report. Data for all five SDGs were analyzed by partial ordering methodology to rank the countries according to their compliance and their trend toward compliance. The analyses took simultaneously data for all five SDGs into account to get an overall picture of the prosperity midway through the 15 years period for the 17 UN SDGs. It was disclosed that the ten top countries, i.e., whose performance presently best meet with the people goals were Singapore > Belarus = Cyprus = Finland = Uruguay > Iceland > New Zealand > Norway > Croatia > China > Argentine, respectively. In the case of the trends, the top countries were found to be Belarus > Croatia = Japan > Belgium = Denmark = New Zealand = Sweden > Estonia, respectively. Ranking the twelve regions it was disclosed that OECD and the high-income countries are the highest ranked whereas Oceania, Africa, and the low-income countries are the lowest ranked and need considerable help to eventually meet the 5 SDGs. It was further disclosed that SDGs 4 and 5 were the most important indicators for the ranking the individual countries, whereas SDG 1 and SDG 5 were the most important for ranking the twelve regions. The importance of gender equality is stressed.